2014
DOI: 10.1111/pin.12173
|View full text |Cite
|
Sign up to set email alerts
|

Gastric‐type endocervical glandular neoplasms associated with aberrant p16 expression and KRAS gene mutation in Peutz‐Jeghers syndrome

Abstract: In this report, unique endocervical glandular lesions exhibiting gastric differentiation were examined in a patient with Peutz-Jeghers syndrome. The result of the human papillomavirus (HPV) in situ hybridization (ISH) for the hysterectomy specimens was negative, but they demonstrated a papillary mucinous adenocarcinoma at the proximal endocervix continuous to atypical lobular endocervical glandular hyperplasia. Both contained MUC6-positive neutral mucin in cytoplasm, and showed different immunoreactivity to p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that p16 and STK11 cell cycle-associated protein was excessively expressed in LEGH lesions. [16][17][18] The results of the present study suggest that the cell cycle in LEGH cells may occur more rapidly than in EC cells; this suggests that mitosis is initiated prior to cell growth in new cells because LEGH cells have more active nuclear division than EC cells and this may explain the smaller nuclear size in LEGH cells.…”
Section: Resultsmentioning
confidence: 57%
“…Previous studies have reported that p16 and STK11 cell cycle-associated protein was excessively expressed in LEGH lesions. [16][17][18] The results of the present study suggest that the cell cycle in LEGH cells may occur more rapidly than in EC cells; this suggests that mitosis is initiated prior to cell growth in new cells because LEGH cells have more active nuclear division than EC cells and this may explain the smaller nuclear size in LEGH cells.…”
Section: Resultsmentioning
confidence: 57%
“…A comprehensive literature search produced 1564 publications; 46 studies were identified that focused on lobular endocervical glandular hyperplasia/gastric-type adenocarcinoma in patients with Peutz-Jeghers syndrome. Thirty-eight (83%) were case reports/case series that met the inclusion criteria and were included in the analysis 13 14 16 19–53. The remaining eight studies were original research (five) or reviews (three) and were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the visible light region, hematoxylin, EA50, and OG6 exhibited maximum absorption at red/green, green, and blue, respectively. On the other hand, LEGH with mutations in either p16 INK4a , KRAS, STK11, GNAS [20][21][22], or minimal deviation adenocarcinoma and other gastric-type adenocarcinomas in the uterine cervix with these mutations have also been reported. Therefore, LEGH is regarded as a neoplastic lesion, not a hyper-plastic lesion [23].…”
Section: Discussionmentioning
confidence: 99%